PERCEIVE OF VULNERABILITY AMONG HIGH RISK PREGNANT MOTHER WHO REFUSE REFERRED TO THE HEALTH FACILITY IN PAITON, PROBOLINGGO, INDONESIA (Proceedings of the International Conference on Public Health, 2017)
Perceive of Vulnerability Among High Risk Pregnant Mother Who Refuse Referred To The Health Facility In Paiton,  Probolinggo, Indonesia . The most important strategy to prevent maternal mortality is early detection high risk pregnancy and prompt treatment. This study aimed to explore the perceive of vulnerability among high risk pregnant mothers who refuse to referred to the health facility. This is a qualitative study conducted on April 2017 in Paiton, Probolinggo, Indonesia. The respondents are head of public health center (PHC), 2 midwifes as key informants and 2 high risk pregnant mothers who refuse to referred to the health facility. Data were collected by in-depth interview and validated using triangulation. Head of PHC is told by mothers that they afraid if their acceptance to be referred to hospital could be a bad signal such as they are delivered home dead or fatal conditions. They belief that refusing is the best choice for their life. Both midwives feel that their condition as high risk pregnant mothers based on the referred standard but mothers still go to other midwife to get second opinion. High risk pregnant mothers say that they are still in a healthy condition and their recent pregnancy do not give bad effect to their life. So, they persist because find their neighbor can deliver normally even she had high risk pregnancy and she can’t handle it if her baby need formula milk. The second mother has a busy husband that can’t drive her to hospital, different perception about hospital choice and perception about delivery baby in hospital only needed by a pregnant mother who got fatal conditions.
Keywords: High Risk Pregnancy, Women